Acute Non Lymphoblastic Leukemia in the Department of Child Health School of Medicine, University of North Sumatera/ Dr. Pirngadi Hospital Medan (1983-1988): A Preliminary Study - Feraluna Nasution; Zairul Arifin; Adi Sutjipto (Indonesian Pediatric Society, 1991)
A retrospective study on Acute Non Lymphoblastic Leukemia (ANLL) was conducted at the Sub Division of Pediatric Hematology, School of Medicine, University of North Sumatera/Dr. Pirngadi Hospital Medan, in a period of 5 years (1983-1988). There were 18 cases consisted of 14 (77. 78%) males and 4 (22 .22%) females with the age group of 0-2 years: 6 (30%), 2-8 years: 9 (50%), 8-15 years: 3 (30%). By the FAB classification, they were of FAB M-1: 1 (5.55%), FAB M-2: 1 (5.55%), FAB M-3: 1 (5.55%), FAB M-4: 2 (11.12%) and FAB M-6: 13 (72.23%). Only 7 (38.88%) were treated with cytostatics while the others received only supportive therapy. The result of cytostatic treatment was unsatisfactory: 4 (57.14%) died within the first 2 months of treatment, 3 (42.86%) discontinued their cytostatics treatment.